Health Promotion Programs From Theory to Practice. - Fertman, Carl I. (New York Academy of Sciences Ser., 2016)
For Practice and Discussion -- Key Terms -- References -- Chapter 3: Theory in Health Promotion Programs -- Theory in Health Promotion Programs -- Foundational Theories/Models: Intrapersonal Level -- Foundational Theories/Models: Interpersonal Level -- Foundational Theories/Models: Population Level -- Foundational Theories/Models Applied Across the Levels -- Health Promotion Program Planning Models -- Using Health Theories and Planning Models -- Summary -- For Practice and Discussion -- Key Terms -- References -- Part 2: Planning Health Promotion Programs